2021
DOI: 10.1159/000518461
|View full text |Cite
|
Sign up to set email alerts
|

Use of Systemic Corticosteroids for Reasons Other than Asthma in Subjects with Asthma

Abstract: <b><i>Backgrounds:</i></b> Recent studies have reported increased risks of adverse events from systemic corticosteroids even with only low-dose or short-term use. Some patients with asthma experience complications requiring systemic corticosteroids. However, few studies have examined issues associated with administration of systemic corticosteroids for reasons other than asthma among subjects with asthma. <b><i>Objectives:</i></b> We investigated patterns of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Subjects with CTDs often receive systemic steroids, immunosuppressants and/or biologics, which result in varying degrees of immunosuppression. In fact, our previous study found that collagen vascular diseases were a risk factor for systemic corticosteroid use in asthma 26 . Respiratory tract infection is the most common cause of asthma exacerbation, 27 and prevention of such infections is important for asthma management.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subjects with CTDs often receive systemic steroids, immunosuppressants and/or biologics, which result in varying degrees of immunosuppression. In fact, our previous study found that collagen vascular diseases were a risk factor for systemic corticosteroid use in asthma 26 . Respiratory tract infection is the most common cause of asthma exacerbation, 27 and prevention of such infections is important for asthma management.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, our previous study found that collagen vascular diseases were a risk factor for systemic corticosteroid use in asthma. 26 Respiratory tract infection is the most common cause of asthma exacerbation, 27 and prevention of such infections is important for asthma management. Moreover, asthma increases the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…To address this concern, we only included systemic steroids prescribed within 28 days of an IBD‐related hospital contact and with the ATC code “H02AB06” in oral tablet form for prednisolone. A study by Watanabe et al 43 that looked at the use of systemic steroids in asthma found that 36.8% of asthmatic patients had received steroids for reasons other than asthma. Therefore, filtering for the relevant dosages from registry data, while challenging, can also greatly alter the results.…”
Section: Discussionmentioning
confidence: 99%
“…A gap of more than 3 months between prescriptions for systemic steroids and a gap of more than 6 months between doses of biologics and immunomodulators were considered as new treatments. 1851 (13) 6149 (43) 3452 (24) 2952 (20) 1687 (6) 251 (14) 918 (15) 1111 (32) 1247 (42) 234 ( 14)…”
Section: Medications and Surgeriesmentioning
confidence: 99%